2021
DOI: 10.3389/fendo.2021.619696
|View full text |Cite
|
Sign up to set email alerts
|

Global Deletion of the Prolactin Receptor Aggravates Streptozotocin-Induced Diabetes in Mice

Abstract: Prolactin (PRL) levels are reduced in the circulation of rats with diabetes or obesity, and lower circulating levels of PRL correlate with increased prevalence of diabetes and a higher risk of metabolic alterations in the clinic. Furthermore, PRL stimulates β-cell proliferation, survival, and insulin production and pregnant mice lacking PRL receptors in β-cells develop gestational diabetes. To investigate the protective effect of endogenous PRL against diabetes outside pregnancy, we compared the number of case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 60 publications
2
5
0
Order By: Relevance
“…Sulpiride improved glucose tolerance and reduced glycemia independently of alterations in body weight and caloric intake in both lean and obese mice. Even if these data are consistent with the beneficial metabolic actions of prolactin [ 13 , 43 ], here we demonstrated that the effects of sulpiride, at least reducing hyperglycemia are independent from PRL actions on its classical receptors, this was concluded because sulpiride reduced glucose levels and improved glucose tolerance in obese mice that are knockout for the prolactin receptors.…”
Section: Discussionsupporting
confidence: 67%
“…Sulpiride improved glucose tolerance and reduced glycemia independently of alterations in body weight and caloric intake in both lean and obese mice. Even if these data are consistent with the beneficial metabolic actions of prolactin [ 13 , 43 ], here we demonstrated that the effects of sulpiride, at least reducing hyperglycemia are independent from PRL actions on its classical receptors, this was concluded because sulpiride reduced glucose levels and improved glucose tolerance in obese mice that are knockout for the prolactin receptors.…”
Section: Discussionsupporting
confidence: 67%
“…PRLR belongs to the cytokine receptor superfamily and has been demonstrated to bind to at least three different ligands, namely prolactin, placental lactogen, and growth hormone, thereby complicating the investigation of its role [ 37 ]. Several studies have investigated the function of PRLR in the regulation of glucose homeostasis, β-cell proliferation, and survival and found that STZ-treated diabetic Prlr–/– mice showed increased glucose levels and impaired glucose intolerance [ 38 , 39 ]. However, the role of PRLR in DN remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Prolactin and placental lactogen stimulate beta cell proliferation and glucose-stimulated insulin secretion and inhibit beta cell apoptosis in rodent islets in vivo and in vitro [ 158 , 159 ] and in some studies of human islets [ 160 , 161 ]. Moreover, lactogen signaling is required for pregnancy-dependent increases in beta cell mass in the mouse and maintenance of maternal glucose tolerance [ 162 , 163 , 164 ]. The effects of prolactin and placental lactogen are mediated through binding to prolactin receptors (PRLRs), which are detected in a wide array of human fetal tissues [ 165 ] including the liver, lung, duodenal villi, adrenocortical cells, renal tubular epithelial cells, skeletal myocytes, and chondrocytes of developing bones.…”
Section: Regulation Of Fetal Insulin Igfs and Igf Binding Proteins By...mentioning
confidence: 99%